Identifying the Chinese Herbal Medicine Network and Core Formula for Allergic Rhinitis on a Real-World Database. (6th November 2020) - Lu, Yen-Chu; Yang, Ching-Wei; Lin, Yi-Hsuan; Hsueh, Ju-Yu; Chen, Jiun-Liang; Yang, Sien-Hung; Chen, Yu-Chun; Chen, Hsing-Yu
Abstract : Background and Purpose . Allergic rhinitis (AR) is a highly prevalent disease, and Chinese herbal medicine (CHM) is commonly used for treating AR. This study aims to demonstrate the CHM network for AR and possible molecular pathways. Materials and Methods . Patients with a primary diagnosis of AR (ICD-9-CM code: 477.9) in 2010 were included, and the National Health Insurance Research Database in Taiwan was used as the data source. Association rule mining and social network analysis were used to establish and explore the CHM network. Possible molecular pathways of the CHM network were summarized and compared with commonly used western medicine (WM) by conducting overrepresentation analysis in the Reactome pathway database. The potential proteins acted by CHMs were obtained from the CHM ingredient-protein databases, including STITCH, TCMSP, TCMID, and TCM@Taiwan. Results . There were 89, 148 AR subjects found in 2010, and a total of 33, 507 patients ever used CHM. On an average, 5.6 types of CHMs were utilized per prescription. Xin-Yi-Qing-Fei-Tang was used most frequently (25.5% of 222, 279 prescriptions), while Xiao-Qing-Long-Tang with Xin-Yi-San was the most commonly prescribed CHM-CHM combination. Up to six distinctive clusters could be found among the CHM network, and core CHMs could be found for AR, such as Xiao-Qing-Long-Tang and Xin-Yi-Qing-Fei-Tang. A total of 140 molecular pathways were covered by the CHM network (2, 432 ingredients from 31 kinds of CHMs), while 39 WMs covered 55 pathways. Among pathways responding to the immune system, WM mainly acted on cytokine signaling-related pathways, while CHM mostly acted on neutrophil/macrophage-related innate pathways and dendritic cell-related adaptive immunity pathways. Conclusion . Our study demonstrated and analyzed the CHM network for AR. Core CHM for AR and possible molecular pathways were presented as well, and this information is crucial for researchers to select candidates for CHM-related studies.